Fabrication and mechanical testing of bioinspired composites - Schooling, Ryan Hilary (Nanyang Technological University, 2024)
Biological ceramic-based composites are often found with complex microstructures, which gives them good mechanical properties like high strength and toughness despite its weak building blocks. However, current efforts to replicate these microstructures have yielded bioinspired composites without the same degree of structure complexity and overall performance. Magnetically assisted slip casting (MASC) is the most promising fabrication method available due to its ability to fabricate microstructures with different orientations between layers. This processing technique uses a rotating magnetic field to manipulate magnetized ceramic microplatelets, giving it the potential of replicating complex microstructures found in nature. In recent studies, the addition of interpenetrating polymer networks (IPN) during the MASC process yielded impressive mechanical properties.